Consumer Responses to CSR in Greek Banking Sector: Does CSR Really Matter? - Xanthopoulou, Panagiota; Alexandros, Sahinidis; Katerina, Stremmenou (European Scientific Journal, ESJ, 2022)
The present study aims to investigate the impact of Corporate Social Responsibility on consumers’ preferences and loyalty in the banking sector. The researchers examined the main concepts associated with CSR and how it is related to the choice and the retention of customers to a specific bank. Qualitative research was implemented by the use of semi-structured interviews with 67 individuals. The purpose of the research was to analyze the extent to which CSR actions affect customers’ choices and loyalty to a bank. The main conclusions that emerged are that although the satisfaction and commitment, as well as the positive perception of consumers, depend on the trust created by the banks, customers in Greece still believe that the CSR actions implemented by banks only contribute to the increase in their organizational profits through the improved corporate reputation and recognition, and thus CSR has not a significant impact on customers’ attraction and loyalty. Finally, it became clear that one of the major problems in the banking sector is the lack of public confidence in the way banks operate and the special role they play in modern societies.